2015
DOI: 10.1093/ehjci/jev288
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of visually assessed apical rocking and septal flash to response and long-term survival following cardiac resynchronization therapy (PREDICT-CRT)

Abstract: A specific LV mechanical dyssynchrony pattern, characterized by ApRock and SF, is associated with a more favourable long-term survival after CRT. Both parameters are also indicators of an effective therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(149 citation statements)
references
References 38 publications
5
140
1
3
Order By: Relevance
“…An example of this is ‘septal flash’: the abnormal brief inward septal motion that occurs during the isovolumic contraction time and which characterises LBBB-related dyssynchrony. An observational study of over 1000 patients (PREDICT-CRT) demonstrated that the presence of apical rocking and septal flash had an incremental value over clinical variables and QRS width for identifying CRT responders (21). In addition, their absence or unsuccessful correction was associated with a high risk for non-response and unfavourable long-term survival.…”
Section: Echocardiographic Assessment Of LV Dyssynchronymentioning
confidence: 99%
“…An example of this is ‘septal flash’: the abnormal brief inward septal motion that occurs during the isovolumic contraction time and which characterises LBBB-related dyssynchrony. An observational study of over 1000 patients (PREDICT-CRT) demonstrated that the presence of apical rocking and septal flash had an incremental value over clinical variables and QRS width for identifying CRT responders (21). In addition, their absence or unsuccessful correction was associated with a high risk for non-response and unfavourable long-term survival.…”
Section: Echocardiographic Assessment Of LV Dyssynchronymentioning
confidence: 99%
“…Apical rocking in multivariable analyses has been associated with fewer major adverse cardiac events in patients receiving CRT . In the recent PREDICT‐CRT trial, absence of apical rocking and unsuccessful correction of the septal flash were associated with a high risk for CRT failure and unfavorable long‐term survival . Unfortunately, inter‐observer agreement for both apical rocking and septal flash was only moderate, with a Kappa value of 0.71, indicating that the assessment of these parameters may not be sufficient in routine practice.…”
Section: Identification Of Electromechanical Dyssynchrony By Echocardmentioning
confidence: 92%
“…The septal flash occurs in the presence of LBBB and is a rapid right‐to‐left motion of the interventricular septum (followed by a rapid return to the right) during the initial (isovolumetric) phase of systole (within the limits of QRS duration) (Figure ). Generally, patients with large septal flash also have a U‐shaped activation and respond better to CRT compared to those with no or little septal flash …”
Section: Septal Flash Septal Rebound Stretch and Apical Rockingmentioning
confidence: 99%
“…Generally, patients with large septal flash also have a U-shaped activation and respond better to CRT compared to those with no or little septal flash. 28,29 The septal rebound stretch is defined as the systolic septal elongation after the initial shortening. 30 Although septal flash and septal rebound stretch are associated in LBBB, their mechanism is different.…”
Section: S Ep Tal Fl a S H S Ep Tal Rebound S Tre Tch And Api Cmentioning
confidence: 99%